2019
DOI: 10.1093/braincomms/fcz049
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical property alterations across the cerebral cortex due to Alzheimer’s disease

Abstract: Alzheimer’s disease is a personally devastating neurodegenerative disorder and a major public health concern. There is an urgent need for medical imaging techniques that better characterize the early stages and monitor the progression of the disease. Magnetic resonance elastography (MRE) is a relatively new and highly sensitive MRI technique that can non-invasively assess tissue microstructural integrity via measurement of brain viscoelastic mechanical properties. For the first time, we use high-resolution MRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 76 publications
5
72
1
Order By: Relevance
“…This work represents the first detailed investigation of the mechanical properties of parcellations of the cerebral cortex, though initial MRE investigations into cortical structure-function relationships Schwarb et al, 2019), contributions to adolescent risk-taking behavior (McIlvain et al, 2020), and the mechanical integrity of the cortex in Alzheimer's disease (Hiscox, Johnson, McGarry, Marshall, et al, 2020) This MRE study is the first to report significant sex differences in viscoelasticity in a wide range of neuroanatomical structures which supplements the wealth of existing data that reports sex differences in neuroanatomy. Interestingly, we found that female brains are approximately 4% more viscous compared to males as indicated by significantly higher ξ in global WM, which contradicts an early study that reported female brains were 9% less viscous in large regions primarily comprising white matter (Sack, Streitberger, Krefting, Paul, & Braun, 2011).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This work represents the first detailed investigation of the mechanical properties of parcellations of the cerebral cortex, though initial MRE investigations into cortical structure-function relationships Schwarb et al, 2019), contributions to adolescent risk-taking behavior (McIlvain et al, 2020), and the mechanical integrity of the cortex in Alzheimer's disease (Hiscox, Johnson, McGarry, Marshall, et al, 2020) This MRE study is the first to report significant sex differences in viscoelasticity in a wide range of neuroanatomical structures which supplements the wealth of existing data that reports sex differences in neuroanatomy. Interestingly, we found that female brains are approximately 4% more viscous compared to males as indicated by significantly higher ξ in global WM, which contradicts an early study that reported female brains were 9% less viscous in large regions primarily comprising white matter (Sack, Streitberger, Krefting, Paul, & Braun, 2011).…”
Section: Discussionmentioning
confidence: 74%
“… Note: Data from these studies have previously been published elsewhere, see Study A = Hiscox et al, 2018; Hiscox, Johnson, McGarry, Marshall, et al, 2020; Hiscox, Johnson, McGarry, Schwarb, et al, 2020; Study B = Schwarb, Johnson, McGarry, & Cohen, 2016; Schwarb et al, 2019, Johnson et al, 2016; Study C = Huesmann et al, 2020; Study D = Burzynska, Finc, Taylor, Knecht, & Kramer, 2017; Study E = Schwarb et al, 2017, Johnson et al, 2018. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic neuroinflammation causes disease-related symptoms, such as loss of neurons and synapses ultimately leading to memory problems and dementia [13]. In addition to the underlying biological processes in AD, the investigation of mechanical properties received attention in recent years as a potential biomarker for early diagnosis, as shown by magnetic resonance elastography (MRE) studies where brain elasticity and viscosity decreased in AD human patients [14,15,16,17,18,19], and as a novel drug target for tissue regeneration [? 20].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these findings suggest that in pathological conditions, adipokines promote Reactive Oxygen Species (ROS) overproduction and inflammatory processes, which are involved in BBB disruption and could potentially act on different brain regions such as the hippocampus ( Figure 4 ). This could explain why metabolic dysfunctions are associated with hippocampus atrophy and with an increased risk of developing dementia and AD [ 113 ]. In this regard, systemic alterations have been correlated to chronic inflammation caused by adiposity [ 114 , 115 , 116 ].…”
Section: Insight Into Alzheimer’s Disease As a Metabolic Disordermentioning
confidence: 99%